Kant e Wittgenstein sobre a necessidade da universalização da moral - Macagnan, Geraldo (2009)
Some questions about morality inside the society will be studied in this paper. The objective here is to show the most important elements about Kantiniana s doctrine and inquiring the doctrine suffer and showing the Wittgenstein s position. Kant shows his doctrine based on the duty. The duty in doing it but not do it together the law, because in this way we would be in the illegality, but it is an obligation that can lead me act independently of my subjective desire, moved only by tendencies. The difference between act by duty and act by morality in legality is act by duty establishing a possibility of universalization in the moral aspect. Doing a balance with this statement I d like to introduce Wittgenstein where he shows his point of view against Katiana s view, saying if we act by duty, the moral rules will be based in punishment and awards, so our moral action will be a negotiation to get something in return. Going besides Kantiana and Wittgensteniana we try to find a relation between traditions and new developments about moral Standards, having in mind the situation faced nowadays in our world, where we studied two new ways to interpret the morality starting in the subject, the emotivism and the relativism. In the relativism we can find the pronouncement that an ethic analysis can t be right or wrong, so we can t say that something is true or false. In the other hand, in the emotivism the rightful or falsity doesn t depend the reasons that support it, but in the subjective wish or the cultural tradition that aggregate on it. The understanding about rationality brings the debate and argument inside the morality s Standards which is a necessity of clarifying. Through the concepts we performed an analysis and we understood its relation and the possibility in a right society and the development in moral standards that overcome some philosophic ideologies that only study the subjective beginning of a moral action.